Ciência, medicina e perícia nas tecnologias de governo - Fonseca , Claudia; Maricato, Glaucia; Costaduarte, Larissa; Riboli Besen , Lucas (Universidade Federal do Rio Grande do Sul, 2016)
Anthropology has been playing a central role in questioning the supposed objective and apolitical character of scientific knowledge by underlining the socio-cultural context and history of the constitution of any scientific theory. From different research universes, anthropologists have sought to demonstrate how science and politics are composed, juxtaposed and produced in the daily work of social actors. In the wake of what Donna Haraway (1995) pointed out, it is there would not be the "science" look, but the look of the scientists - always located in a space (which is not only geographical, but temporal, cultural, marked by social differences, etc.). It is therefore based on the premise that science and are mutually constituted and from specific contexts. Following In this line, this collection explores how certain knowledges are constituted and legitimized, how technologies of government come into action - and, through practices of the social agents, are (re) formulated - and how through such devices new categories of analysis, social markers, populations and subjectivities (FONSECA, MACHADO, 2015)